Differences in physiological parameters between treadmill running and treadmill roller skiing in nordic skiers - Hill, M. R.; Gregory, R. W.; Amico, V. J.; Osbeck, J. S.; Goodwin, G. T.; Rundell, K. W. (Medicine & Science in Sports & Exercise, 1995)
Peak physiological parameters for ski skating on roller skis are different to those obtained during treadmill running. This suggests that sport specific testing should be done when determining sport specific training intensities. Implication: The physiological factors involved in roller skiing are very specific for the activity and cannot be inferred from running treadmill tests.